Benefits of pre-operative concurrent chemo-radiotherapy among elder patients with local advanced rectal cancer - Wen-Chien Ting; Chih-Jung Yeh (International Journal of Management, Economics and Social Sciences (IJMESS), 2018)
The pre-operative chemo-radiotherapy (Pre-OP CCRT) in aged patients with stage III rectal cancer may be less effective. We collected data from 3365 patients (2004-2012) from Taiwan Cancer Registry. Metachronous colorectal cancer and multiple cancer patients were excluded. The patients were separated in three groups, operation first, Pre-OP CCRT first and treatment without operation. SAS 9.2 Student-t, ANOVA and Chi-Square tests were used for analysis. It was found that Group II had good survival curve than the group I (HR =0.26, p<0.0001). The group III had the worst survival benefit (HR=3.38, p<0.0001). Patients with age <75 Y/O had the same survival curve (p=0.0099). Patients age between75-80Y/O had worse survival time (HR=2.91, p<0.0001). The mortality rate increased dramatically in patients old than 85Y/O but the Pre-OP CCRT still provided survival benefit (HR=6.55, p<0.0001). Pre-operative CCRT improved survival in stage III rectal cancer. Even patients with 80~85 years old still had the benefit. In old patients without major comobility and good physical status, Pre-OP CCRT was still the best choice.
Keywords: 330; Pre-operative concurrent chemo-radiotherapy (Pre-op CCRT); rectal cancer; local recurrence; survival time